Viabilidade econômica do uso de cereais irrigados na produção de etanol - Chaiben Neto, Miguel (2022)
The state of Rio Grande do Sul has an ethanol production of less than 1% of its demand, this is due to the fact that sugarcane, the main raw material used in Brazil, does not adapt well to the state's climate. However, other raw materials can be used in the production of ethanol, such as starch, which are used in different countries. However, it is necessary to evaluate the technical and economic feasibility of these alternative raw materials to sugarcane. In view of the above and considering the climatic conditions of the state of Rio Grande do Sul, the present study aims to evaluate the economic viability, morphophysiological properties and yield of corn and grain sorghum crops irrigated with different irrigation depths for the production of ethanol. Experiments were carried out with corn and grain sorghum crops during the 2019/20 and 2020/21 harvests, in an experimental area of the Colégio Politécnico da UFSM.. The experiments were arranged in a bifactorial arrangement, in strips with randomized blocks and four replications. Where the influences of three irrigation depths were evaluated in factor "A": 0%, 50% and 100% of the reference evapotranspiration and for factor "D" the responses of two maize cultivars and one grain sorghum cultivar were evaluated. . The experimental units were 4 m wide and 4 m long. For the analysis of economic viability, 45 scenarios were elaborated, evaluating three conditions of raw materials, three irrigation depths and five values of ethanol commercialization, being the value of 3.00 R$.L-1 considered as standard. The irrigation depth of 100% water replacement provided an increase of 46.8% in ethanol productivity for crops. The 50% water replacement depth showed results 15.3% higher than the other depths for water productivity and economic water productivity. The corn crop had the best performance for grain yield, ethanol yield, water yield and economic water yield, when compared to grain sorghum. The use of full irrigation reduces the production costs of a liter of ethanol by 15% and 17.89% and increases ethanol production by 44.18% and 48.25% for corn and grain sorghum crops, respectively. For the commercialization price of R$ 2.00 L-1, the grain sorghum crop does not show good performance, showing negative NPV and IRR. On the other hand, corn is economically viable for ethanol production in all scenarios, with positive results for all indicators. The corn crop with full irrigation and commercialization price of R$ 4.00 L-1, represents the best economic scenario, with higher results in all indicators.